2011
DOI: 10.5194/acp-11-7727-2011
|View full text |Cite
|
Sign up to set email alerts
|

The influence of semi-volatile and reactive primary emissions on the abundance and properties of global organic aerosol

Abstract: Abstract.Semi-volatile and reactive primary organic aerosols are modeled on a global scale using the GISS GCM II' "unified" climate model. We employ the volatility basis set framework to simulate emissions, chemical reactions and phase partitioning of primary and secondary organic aerosol (POA and SOA). The model also incorporates the emissions and reactions of intermediate volatility organic compounds (IVOCs) as a source of organic aerosol (OA), one that has been missing in most prior work. Model predictions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
127
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(131 citation statements)
references
References 76 publications
(135 reference statements)
4
127
0
Order By: Relevance
“…Traditionally, models have tended to predict a predominance of POA over SOA (Chung and Seinfeld, 2002;Kanakidou et al, 2005;Pun et al, 2003;Vutukuru et al, 2006), but measurement studies show striking evidence of SOA dominance observed at various locations, even in heavily urbanized locations (Zhang et al, 2005de Gouw et al, 2005;Volkamer et al, 2006). Recent work has suggested that many global models are underestimating OA sources (Heald et al, 2010;Spracklen et al, 2011b) that appear to be SOA, and recent improvements in SOA modeling efforts have addressed this discrepancy (Jathar et al, 2011;Pye and Seinfeld, 2010). To complicate the matter even further, different measurement techniques result in different SOA/OA fractions, as was the case for the Pittsburgh Air Quality Study, for which SOA/OA values were estimated to be 35-73 % (Subramanian et al, 2007;Cabada et al, 2004;Shrivastava et al, 2007;Zhang et al, 2005).…”
Section: W Trivitayanurak and P J Adams: Does The Poa-soa Split Mamentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, models have tended to predict a predominance of POA over SOA (Chung and Seinfeld, 2002;Kanakidou et al, 2005;Pun et al, 2003;Vutukuru et al, 2006), but measurement studies show striking evidence of SOA dominance observed at various locations, even in heavily urbanized locations (Zhang et al, 2005de Gouw et al, 2005;Volkamer et al, 2006). Recent work has suggested that many global models are underestimating OA sources (Heald et al, 2010;Spracklen et al, 2011b) that appear to be SOA, and recent improvements in SOA modeling efforts have addressed this discrepancy (Jathar et al, 2011;Pye and Seinfeld, 2010). To complicate the matter even further, different measurement techniques result in different SOA/OA fractions, as was the case for the Pittsburgh Air Quality Study, for which SOA/OA values were estimated to be 35-73 % (Subramanian et al, 2007;Cabada et al, 2004;Shrivastava et al, 2007;Zhang et al, 2005).…”
Section: W Trivitayanurak and P J Adams: Does The Poa-soa Split Mamentioning
confidence: 99%
“…Traditional global models that have included SOA produced from "traditional" anthropogenic organic precursors (i.e., single compounds with well-characterized smog chamber yields such as aromatics) have predicted that these make a small contribution (about 10 %) to global OA sources (Tsigaridis and Kanakidou, 2003;Farina et al, 2010), so they are not considered here. Potentially much larger sources of anthropogenic SOA from IVOC oxidation (Jathar et al, 2011;Pye and Seinfeld, 2010) are considered in the sensitivity studies (see Sect. 2.4).…”
Section: Secondary Organic Aerosolmentioning
confidence: 99%
“…3370 A. P. : an efficient module to compute volatility and oxygen content approach, semi-volatile primary emissions, chemical aging, and SOA formation were unified within a common framework that is ideally suited for regional and global chemical modeling. Since 2006, many regional (Lane et al, 2008;Murphy and Pandis, 2009;Tsimpidi et al, , 2011Ahmadov et al, 2012;Athanasopoulou et al, 2013;Koo et al, 2014;Fountoukis et al, 2014;Ciarelli et al, 2017;Gao et al, 2017) and global (Pye and Seinfeld, 2010;Jathar et al, 2011;Jo et al, 2013;Tsimpidi et al, 2014;Hodzic et al, 2016) modeling studies have used the VBS to account for the semi-volatile nature and chemical aging of organic compounds, demonstrating improvements in reproducing the OA budget and its chemical resolution.…”
Section: Introductionmentioning
confidence: 99%
“…This framework describes the OA absorptive partitioning, where OA is assumed to be semivolatile and photochemically reactive and is distributed in logarithmically spaced volatility bins. With this approach, the intermediate and semivolatile primary emissions and the SOA formation and its chemical aging can be simulated in a common framework that is well suited for regional and global modeling (Murphy and Pandis, 2009;Jathar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%